Photographic Visibility of Indian Politicians, Cricketers, and Film Stars in Print Journalism - Koley, Susanta; Goswami, Sutapa (Information Research Communications, 2025)
Background Eugene Garfield and M. V. Malin’s (1968) pioneering study, “Can Nobel Prize Winners Be Predicted?”, was an early and influential attempt to correlate citation frequency with the likelihood of receiving prestigious scientific honors. Their work laid the groundwork for the use of citation analysis as a means of evaluating scholarly prominence and forecasting future recognition. This analytical framework was later adapted beyond the scientific domain, with Sen and Munshi (2001) applying similar quantitative techniques to analyse the visibility patterns of Indian political leaders. Aim The aim of this study is to re-emphasize the significance of the visibility index as a valuable tool in bibliometric research, particularly for audiences in Library and Information Studies. This will be demonstrated through the analysis of images of political, sports, and film personalities as featured in newspapers. Materials and Methods This study analyses 1373 photographs of Indian public figures from politics, cricket, and cinema, as featured in five Kolkata-based daily newspapers-The Statesman, The Times of India (English), Anandabazar Patrika, Bartaman, and Eai Samay (Bengali)-between February 5 and 18, 2025. Of the 1,373 images, 695 were political figures (165 unique individuals), 434 from cinema (177 individuals), and 244 cricketers (40 individuals). Data were tabulated using MS Word and Excel, and the Visibility Index by Sen and Munshi (2001) was applied for analysis. Results The analysis of 1,373 newspaper photographs reveals that political figures dominated media visibility, accounting for 50.62% of the 1,373 images, with 165 unique individuals. Cinema followed with 31.61% (177 individuals), and cricket had 17.77% (40 individuals). Prime Minister Narendra Modi had the highest visibility (137 mentions, VI 1.96), followed by Mamata Banerjee (86 mentions, VI 1.23). In cricket, Rohit Sharma led (44 mentions, VI 0.63). Film coverage was more fragmented, and no actor showed sustained visibility, indicating a strong editorial focus on political figures, a personality-driven approach in sports coverage, and sporadic attention to film celebrities. Conclusion The study reveals a strong media bias toward politics, with national leaders dominating visibility. Cricket shows more balanced but event-driven coverage, while film personalities receive fragmented, short-lived attention. Overall, media visibility is personality-driven rather than domain-based, raising concerns about representational imbalance.
Keywords: Bibliometrics; Cricketers; Film Stars; India; Informetric; Newspapers; Photographic visibility; Politicians; Print media; Visibility index.